The effect of the crow hop on elbow stress during an interval throwing program - Lizzio, V. A.; Smith, D. G.; Guo, W. E.; Cross, A. G.; Gulledge, C. M.; Koolmees, D. S.; Chalmers, P. N.; Makhni, E. C. (The American Journal of Sports Medicine, 2021)
Background: Postoperative rehabilitation protocols after ulnar collateral ligament (UCL) reconstruction typically involve a structured interval throwing program. In an effort to minimize torque placed on the UCL, athletes are often instructed to throw with a crow hop, even at short throwing distances. However, the effect of the crow hop on medial elbow stress is unknown.